A Sociological Criticism of the Global Health Discourse: The Pandemic as a Metaphor of Contemporary Culture - Sertaç Timur Demir (İstanbul Üniversitesi Sosyoloji Dergisi)
This article argues that a clear correlation exists between disease and the prevailing social functioning. In this respect, every disease can be seen as a metaphor for the age and society in which it emerges. In other words, every period carries a form of disease that bears traces of the dominant lifestyle. This study approaches the epidemic as a kind of sociological projection in the context of studying modern culture and continues the discussion along the lines critically opened by Susan Sontag (2005). Just as Sontag examined disease as a metaphor, this article debates the discourses on masks, social distancing, and hygiene within the scope of COVID-19 along a specific sociological axis around the concepts of speed, control, information, hypermedicalization, and death as the dominant indicators of contemporary culture. For this purpose, the study seeks answers to the following questions through the leading social theorists of the field such as Bauman, Baudrillard, Turner, Furedi and ChulHan: How does the global epidemic and the current health discourse embodied in it appear within the sociological context? What thoughts and tendencies emerge when examining the pandemic portrait as a social metaphor? For example, what kind of relationship exists between hygiene and cultural fears; among distance, social isolation, and avoidance; and between masks and the superficial idea of death concealed behind quantification? Undoubtedly, the pandemic is a critical breaking point in the history of modern medicine and has forced not only global health practices but also many value judgments to both paradoxically be accepted and questioned.